1962
DOI: 10.1172/jci104645
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Chylomicron Cholesterol Ester in the Rat

Abstract: The lymphatic transport of cholesterol is of great quantitative importance in the over-all metabolism of cholesterol. It is now well established that exogenous cholesterol is absorbed almost exclusively by way of the intestinal lymph (1, 2), where most of the newly absorbed cholesterol is found esterified, in the chylomicron fraction (3,4). Estimates of the extent of esterification have varied from 90 per cent at the peak of cholesterol absorption (3) to an average of 72 + 6 per cent over a wide range of absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0
1

Year Published

1965
1965
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(42 citation statements)
references
References 21 publications
8
33
0
1
Order By: Relevance
“…These correlations suggest that the hepatic enzyme plays a role in the process of chylomicron remnant removal from plasma. It has been established that chylomicron remnants avidly interact with specific receptors on hepatocytes, and that this interaction is followed by rapid uptake and degradation ofthe particles (3,32,34,36). Our data suggest that before their catabolism via the receptormediated pathway that the chylomicron remnant particles interact with HTGL.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These correlations suggest that the hepatic enzyme plays a role in the process of chylomicron remnant removal from plasma. It has been established that chylomicron remnants avidly interact with specific receptors on hepatocytes, and that this interaction is followed by rapid uptake and degradation ofthe particles (3,32,34,36). Our data suggest that before their catabolism via the receptormediated pathway that the chylomicron remnant particles interact with HTGL.…”
Section: Discussionmentioning
confidence: 54%
“…Initially, the particles interact with lipoprotein lipase in extrahepatic tissues resulting in triglyceride hydrolysis and delivery offree fatty acids to the tissues (1, 2, 31). After most triglycerides are hydrolyzed, remnant particles are formed (3,32) that are removed from the circulation by hepatocyte receptors that recognize apo E (33)(34)(35)(36)(37). The exact stage when chylomicrons become remnants is not known, and there are no methods currently available to physically separate the two.…”
Section: Discussionmentioning
confidence: 99%
“…35 " 37 Nestel et al 38 showed in dogs that functional hepatectomy caused a retention in the serum of cholesteryl esters, but not of triglycerides, after the injection of chylomicrons. This observation was confirmed in rats by Redgrave. 39 Mjas et al 40 isolated remnant particles of intestinal origin after an injection of chylomicrons in functionally hepatectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…From lymph duct cannulation studies in our laboratory, chylomicrons from ACAT2 Ϫ / Ϫ mice have more TG mass compared with wildtype mice ( 8 ). However, due to rapid and effi cient clearance of chylomicron remnants from the circulation by liver ( 22,23 ), this would not appear to be a major mechanism of TG increase in the plasma. It is possible that, as a result of chylomicrons delivering less CE to the liver in ACAT2 SI Ϫ /SI Ϫ mice, a CE-poor lipid droplet may result in the liver, leading to a similar effect on TG mobilization as was observed in mice with the loss of hepatic ACAT2 ( 6,7 ).…”
Section: Have Lower Levels Of Biliary Cholesterolmentioning
confidence: 99%